Young aged children ependymomas - Orlov, Yu. A.; Shaversky А. V.; Plavsky, P. N. (Ukrainian Neurosurgical Journal, 2007)
Ependymomas are not rare glial brain tumours and occupy the third place among formations in children population. The nature of their origin, histobiological classification and treatment are still under discussion. In spite of some treatment achievements, prognosis in case of ependymoma is bad. The basic prognostic factor for these tumours treatment — is their radical removal. The experience of diagnostics and treatment of 34 young aged children with brain ependymomas is given. The invasive character of tumour growth substantiates the application of combined treatment including operation, chemotherapy, and radiation therapy if it is possible.